Energy performance analysis of buildings in terms of alternative reinforced concrete structural systems - Tutumlu, Hakan; Aydoğdu, Berkay; İnallı, Mustafa (My University, 2022)
In this study, the thermal energy performances and environmental effects of two different reinforced concrete structures, Pure Shear Wall (PSW) Building and Shear Wall-Frame (SWF) Building, were investigated in the climatic conditions of Elazig province. Thermal performance analysis for both buildings; was carried out with the TS 825 program. First of all, through this program, monthly and annual heating loads were determined for 11 different alternative building component scenarios of two different buildings. Subsequently, efficiency alternatives were created in accordance with the climatic conditions of the region and TS 825. Efficiency alternatives designed for both buildings have been analyzed together with their completely uninsulated and current states. Finally, buildings with reinforced concrete carrier systems, energy analysis methods and efficiency alternatives were compared and evaluated based on the results of the analysis. As a result, it has been observed that the building with the PSW system consumes more energy than the building with the SWF system when it is uninsulated and in its current condition.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Pure shear wall; Shear wall-frame; TS825; Performance analysis and insulation